A Pulsed Electromagnetic Field Protects Against Glutamate-induced Excitotoxicity by Modulating the Endocannabinoid System in HT22 cells - Li, Xin; Xu, Haoxiang; Lei, Tao; Yang, Yuefan; Jing, Da; Dai, Shuhui; Luo, Peng; Xu, Qiaoling (Frontiers in Neuroscience, 2017)
Glutamate-induced excitotoxicity is common in the pathogenesis of many neurological diseases. A pulsed electromagnetic field (PEMF) exerts therapeutic effects on the nervous system, but its specific mechanism associated with excitotoxicity is still unknown. We investigated the role of PEMF exposure in regulating glutamate-induced excitotoxicity through the endocannabinoid (eCB) system. PEMF exposure improved viability of HT22 cells after excitotoxicity and reduced lactate dehydrogenase release and cell death. An eCB receptor 1 (CB1R) specific inhibitor suppressed the protective effects of PEMF exposure, even though changes in CB1R expression were not observed. Elevation of N-arachidonylethanolamide and 2-arachidonylglycerol following PEMF exposure indicated that the neuroprotective effects of PEMF were related to modulation of the eCB metabolic system. Furthermore, CB1R/ERK signaling was shown to be an important downstream pathway of PEMF in regulating excitotoxicity. These results suggest that PEMF exposure leads to neuroprotective effects against excitotoxicity by facilitating the eCB/CB1R/ERK signaling pathway. Therefore, PEMF may be a potential physical therapeutic technique for preventing and treating neurological diseases.